Consumerscapes and the cultural logic of shopping places - Cachinho, Herculano (2019)
This paper sketches a consumer-centric approach of urban retailing, broadening the conceptual framework of the Consumer Culture Theory (CCT) developed by Eric Arnould for stores to the shopping districts. We intend to show why consumerscapes matter for understanding the cultural dimension of urban retailscapes and the role they play in the consumers’ daily-lives. In this context we briefly describe the CCT and its potential for the assessment of shopping places as fields of resources. The discussion will be conducted both in a theoretical and empirical way, supported by a case study analyzing consumers’ perceptions of Colinas do Cruzeiro, a quarter situated in the outskirts of Lisbon.